A pyrene-based electropolymerized film as a solid-state platform for multi-bit memory storage and fluorescence sensing of nitroaromatics in aqueous solutions12. Issue 19 (15th April 2016) - Chhatwal, Megha; Kumar, Anup; Gupta, Rinkoo D.; Awasthi, Satish K.
Abstract : Elucidation of multi-state memory storage and sniffing of nitroaromatics by an osmium-based polypyrene film on ITO-coated glass electrodes. Abstract : A polypyrene film of an osmium–terpyridine complex is deposited via anodic electropolymerization on ITO-coated glass electrodes. The optical properties of the film were electrically modulated to generate quintuple absorbance states, making the film a potential molecular alternative to silicon-based static random access memory (SRAM) devices. Moreover, the film could perceive nitroaromatics up to parts-per-million level concentrations in aqueous medium via fluorescence quenching.